The Effect of Online Core Courses Enrollment on Student Success: The Case of University System of Georgia. Issue 4 (1st October 2020) - Lee, Daewoo; Combes, Nathan
ABSTRACT: This study examines the impact of online core courses on students' academic and financial outcomes of postsecondary students. To do so, we analyzed data from a large sample of students in the University System of Georgia (USG), governing agency of Georgia's 26 public universities and colleges. Since 2001, USG has offered "eCore" courses: lower-division core curriculum courses that are offered fully online to students enrolled in either face-to-face or fully online programs, and satisfy requirements at any USG institution. Our dataset contains students seeking associate degrees (N = 103, 684) and bachelor's degrees (N = 238, 648) analyzed independently. Our research investigates the impact that eCore has on student retention, graduation, and loan accumulation. Our findings show that students who took eCore courses enrolled in more semesters regardless of the degree being sought. Associate-seeking students who enrolled in eCore courses were more likely to graduate and took on fewer loans on average.